The Canadian Electronic Ensemble: Past, Present, and Future: Panel Discussion - Stillwell, Paul; Montgomery, Jim; Jaeger, David; Gale, Emily (Intersections, 2021)
In this panel discussion Paul Stillwell, Jim Montgomery, and David Jaeger discuss their experiences in the experimental and electroacoustic scenes, including reflections on technologies, collaborators, and tours. Dr. Emily Gale served as moderator. This panel discussion has been edited for clarity.